Evaluating the ionospheric mass source for Jupiter's magnetosphere: An ionospheric outflow model for the auroral regions - Martin,CJ; Ray,LC; Constable,DA; Southwood,DJ; Lorch,CTS; Felici,M (Journal of Geophysical Research: Space Physics, 2020)
Ionospheric outflow is the flow of plasma initiated by a loss of equilibrium along a magnetic field line which induces an ambipolar electric field due to the separation of electrons and ions in a gravitational field and other mass dependant sources. We have developed an ionospheric outflow model using the transport equations to determine the number of particles that flow into the outer magnetosphere of Jupiter. The model ranges from 1400 km in altitude above the 1 bar level to 2.5 RJ along the magnetic field line and considers H+ and H3+ as the main ion constituents. Previously, only pressure gradients and gravitational forces were considered in modelling polar wind. However, at Jupiter we need to evaluate the affect of fieldaligned currents present in the auroral regions due to the breakdown of corotation in the magnetosphere, along with the centrifugal force exerted on the particles due to the fast planetary rotation rate. The total number flux from both hemispheres is found to be 1.31.8 x 1028 s1 comparable in total number flux to the Io plasma source. The mass flux is lower due to the difference in ion species. This influx of protons from the ionosphere into the inner and middle magnetosphere needs to be included in future assessments of global flux tube dynamics and composition of the magnetosphere system.